2004
DOI: 10.1113/jphysiol.2004.061762
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral anion transport mechanisms underlying fluid secretion by mouse, rat and guinea‐pig pancreatic ducts

Abstract: Fluid secretion by interlobular pancreatic ducts was determined by using video microscopy to measure the rate of swelling of isolated duct segments that had sealed following overnight culture. The aim was to compare the HCO 3 − requirement for secretin-evoked secretion in mouse, rat and guinea-pig pancreas. In mouse and rat ducts, fluid secretion could be evoked by 10 nM secretin and 5 µM forskolin in the absence of extracellular HCO 3 − . In guinea-pig ducts, however, fluid secretion was totally dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 38 publications
(58 reference statements)
3
58
0
Order By: Relevance
“…Remarkable differences in the expression of NKCC1 in the glandular epithelia of various species and organs can be observed. NKCC1 can be found in the basolateral membranes of rat and mouse pancreatic ducts, but not in the pancreatic and salivary gland duct cells of pig and guinea pig (17,40,41). Our present work evidenced the expression of NKCC1 in the basolateral membranes of both acinar and duct cells from rabbit LG by immunofluorescence with stronger staining observed in acinar cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Remarkable differences in the expression of NKCC1 in the glandular epithelia of various species and organs can be observed. NKCC1 can be found in the basolateral membranes of rat and mouse pancreatic ducts, but not in the pancreatic and salivary gland duct cells of pig and guinea pig (17,40,41). Our present work evidenced the expression of NKCC1 in the basolateral membranes of both acinar and duct cells from rabbit LG by immunofluorescence with stronger staining observed in acinar cells.…”
Section: Discussionsupporting
confidence: 55%
“…In a recently published paper by our laboratory, video-microscopic technique was adapted and was used for the first time in lacrimal duct research to investigate fluid secretion of isolated LG duct segments (13). This technique was originally developed by Fernandez-Salazar et al for the measurement of fluid secretion of pancreatic ducts (14).…”
Section: Role Of Lg Ducts In Lacrimal Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFTR from eutherian mammals also has a relatively low P HCO3 (Gray et al, 1993;Gray et al, 1990;Linsdell et al, 1997;O'Reilly et al, 2000;Poulsen et al, 1994). However, in the pancreatic duct cells it has been suggested that HCO 3 -secretion occurs via CFTR because there is no mechanism on the basolateral membrane to accumulate Cl -, whereas there is a mechanism for HCO 3 -accumulation (Fernández-Salazar et al, 2004). As a result, following stimulation of CFTR, the intracellular Cl -activity ([Cl -]i) rapidly falls and approaches its equilibrium value, thus there is no driving force for Cl -exit across the apical membrane via CFTR (Ishiguro et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…Latter studies isolated ducts by microdissection from pancreas of rats, guinea pigs, and mice partially digested with collagenase. Secretin has been shown to stimulate bicarbonate fluid in the isolated duct fragments by microperfusion and by letting the ends of the ducts seal in culture after which the volume increase can be monitored by video microscopy and the ion content sampled by micropuncture (3,34,46). Guinea pig ducts have been especially useful because they secrete a high concentration of bicarbonate similar to humans while rats and mice secrete lower amounts (100).…”
Section: In Vitro Studies Of Secretin Action On Pancreatic Ductsmentioning
confidence: 99%